ANALISIS PENGARUH KEPUASAN KONSUMEN TERHADAP LOYALITAS PELANGGAN DENGAN KUALITAS PRODUK SEBAGAI VARIABEL MEDIASI - Dyah Ayu Dwi Kusumawati (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The purpose of this study was to analyze the significance of the effect of customer satisfaction with the quality of products to customers Oryza Florist Surakarta. Analyze the significance of the effect of customer satisfaction on customer loyalty in customers Oryza Florist Surakarta. Analyze the significance of the effect of product quality on customer loyalty in customers Oryza Florist Surakarta. Analyze the significance of the effect of customer satisfaction on customer loyalty mediated by the quality of products to customers Oryza Florist Surakarta. In conclusion: Customer satisfaction is a significant effect on the quality of the product on a series of services in Oryza Florist flower bouquet Surakarta. Significant effect of customer satisfaction on customer loyalty in services bouquet flower arrangement in Oryza Florist Surakarta. Quality products have a significant effect on customer loyalty in services bouquet flower arrangement in Oryza Florist Surakarta. Quality products mediate the effect of customer satisfaction on customer loyalty in services bouquet flower arrangement in Oryza Florist Surakarta. Keywords: Customer Satisfaction, Product Quality and Customer Loyalty